Seasonal changes in the density and species composition of the epifaunal echinoderms recorded from the southwestern Gulf of Mexico - Vázquez-Bader, A. R. (2008)
The distribution and relative abundance of epifaunal echinoderms in the Southwestern region of the Gulf of Mexico based on 181 collections by the use of an Otter Trawl during different years are described. A total of 59 species were recorded, and represent the following five classes; Asteroidea 25 species, Ophiuroidea 15 species; Echinoidea 14 species, Crinoidea 4 species, and Holothuroidea 1 species. The most frequently encountered single species was Luidia clathrata found at 68 % of all the stations sampled. Furthermore, Astropecten nitidus Astropecten duplicatus, Mellita quienquiesperforata, Brissopsis atlantica, Brissopsis elongata, Astropecten articulatus, Luidia alternata, Comactinia meridionalis, Astropecten alligator, Astropecten cingulatus, Tethyaster grandis, and Clypeaster ravenelii, were species less abundant and frequent and accounted for 13% of the remaining percentage of the echinoderms collected and identified. The starfish Luidia clathrata was the largest species size collected on the Campeche Bank at 16 m depth. The highest seasonal density of the echinoderms was recorded in Autumn on carbonate substrate, whereas the highest species richness was found in summer. Rev. Biol. Trop. 56 (Suppl. 3): 297-310. Epub 2009 January 05.